Community Based Physical Exercise Program for The Elderly in South India - Lakshminarayanan Subitha; Soudarssanane M Bala; Murugesan Ramanujam (Medsci Publications, 2012)
Context: Physical inactivity is an important risk factor for hypertension, osteoarthritis, diabetes and cardiovascular diseases among elderly. Aims:This study was done to study the feasibility of implementing of a community based geriatric exercise program by providing Bicycle Ergometers and to assess the reduction in blood pressure. Settings and Design: Community based intervention study Methods and Material:This study was carried out in four phases, awareness campaign, recruitment and baseline assessment, intervention (10 weeks) and final assessment.Three bicycle ergometers were placed in the community hall and made accessible during fixed timings. Sixty subjects > 60 years were allotted to six groups based on their convenience of exercise timings. Members of self help groups, youth clubs and other volunteers were trained on assisting and supervising exercise sessions. Ten minutes per exercise session for three sessions a week included warm-up period, main period of cycling, and cool-down period. Statistical analysis used: Analysis was done using paired 't' test. Results: Mean age of participants (28 males, 32 females) was 64.6 years. Drop out rate was 37%; 22 subjects (37%) engaged in > 3 sessions per week, while 26 % participated in 1-3 sessions during the intervention. Per protocol analysis on 38 participants who completed intervention, showed a significant reduction in mean BP by 4.18/ 2.02 mm Hg (p=0.000). Conclusions:This study has proved the functional feasibility of enabling elderly people to undertake physical activity in a rural Indian community, and the effectiveness of physical activity in significantly reducing mean blood pressure levels.